Spin–orbit-induced hole spin relaxation in a quantum dot molecule: the effect of s-p coupling. (17th June 2019) - Kawa, Karol; Machnikowski, Paweł
Abstract: We study the effect of the coupling between the hole s shell of one quantum dot and the p   shell in the other dot forming a vertically stacked self-assembled quantum dot molecule on the spin relaxation between the sublevels of the hole s state. Using an effective model that captures the spin–orbit effects in the p   shell irrespective of their origin, we show that the strong spin mixing in the p   shell can be transferred to the s shell of the other dot, leading to enhanced spin relaxation in a certain energy range around the s - p   resonance if the dots are misaligned and the magnetic field is tilted from the sample plane.